PERANAN SYEIKH H. ABDUL WAHID AL-FATTAH DALAM MENYEBARKAN AJARAN AGAMA ISLAM DI KECAMATAN KUBU (1950-2004) - Hasanah, Lailatul; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrackt: Islam is a religion of nature that Allah SWT revealed to Rasullulah to be submitted to his people. The birth of the Islamic religion brought by the messenger of Allah SWT in the 7 th century Ad resulted in an extraordinary power that has been experienced by mankid. One of them is Sheikh H. Abdul Wahid Al-Fattah who spread the Islamic agma in district of Kubu especially in Rantau Panjang Kiri sub-districk, precisely in Rantau Panjang Kiri bay Village. The purpose of his research is 1) To know the history of Syeikh H. Abdul Wahid Al-Fattah 2) To know the role of Syeikh H. Abdul Wahid Al-Fattah in spreading Islam in district Kubu regency 3) To know what barriers felt by Syeikh H. Abdul Wahid Al-Fattah develop Islam in district Kubu regency. As for the benefis of research 1) As an input forvthe writing of local history and national history generally 2) to deepen science especially for the writer humself in the field of reseach 3) knowing the struggle of Syeikh H. Abdul Wahid Al-Fattah in the spread of Islam . In the study using qualitative research methods. Qualitative is a method that does not use number in data collections and in providing interpretation of the results. The result of this study is Syeikh H. Abdul Wahid Al-Fattah is a scholar, in mengehbarkan Islam religion in the district of Kubu in 1950-2004 M. the role of Syeikh H. Abdul Wahid Al-Fattah teaching for the people of district Kubu village can be seen from the efforts made in the field of education and da’wah, has brought great changes to the district Kubu community, especially in the village of Rantau Panjang Kiri.Keywords: Position, spread of Islam